Pemanfaatan Open Course Ware dalam Penggunaan Uji Profisiensi Sertifikasi Bidang Informatika - Amanto .; Rangga Firdaus - Universitas Negeri Lampung (Indonesian Journal of Networking and Security (IJNS), 2018)
Abrstact - This article is a continuation of the first year publication, what has been produced in the first year is to have created a platform in terms of Open Course Ware (OCW) Design in the Application of Private Cloud Computing-based Content Management Application (CMA) to Assist Test Preparation Certification to the Professional Certification Institute for Students of the Informatics Study Program in Indonesia. In this advanced research focuses on the addition and development of the content of the certification test material on the association and application of the results of the platform to all Informatics study program students in Indonesia based on the existing competency scheme. In accordance with Ministry of Research and Technology regulation number 44 of 2015 concerning National Standards of Higher Education, the teaching and learning process refers to the form of Student Learning Centered (SCL), where students must be active in the teaching and learning process. Students graduated have the right to obtain a diploma, professional certificate, and competency certificate. Competency certificates are issued by universities in collaboration with professional organizations, training institutions, accredited professional certification institutions. Of the various problems of the existing Weaknesses, there must be an effort to resolve them, the emergence of the concept of Open Course Ware (OCW) as a new platform in the field of educational technology has several general characteristics that distinguish it from other learning system management, including (1) Offered Free, (2) No Register, (3) Openly Lisenced, (4) Accessible to anyone, (5) Extraordinary, this research is expected to help contribute as a solution to improve the competence of Indonesian workers, through the Open Course Ware Design (OCW) in application content management application (CMA) to assist in the preparation of competency tests for students from informatics study programs in Indonesia, the system design method used is the prototype method. The results obtained are the application of an integrated system in an OCW system that implements and develops existing content. Keywords; Open Course Ware, Test Certification, Competence, Informatics, Educational Technology Abrstak - Artikel ini merupakan lanjutan dari publikasi tahun ke-1, hal yang telah dihasilkan dalam tahun pertama adalah telah membuat suatu platform dalam hal Perancangan Open Course Ware (OCW) dalam Penerapan Content Management Application (CMA) berbasis Private Cloud Computing untuk Membantu Persiapan Uji Sertifikasi pada Lembaga Sertifikasi Profesi bagi Mahasiswa Program Studi Informatika Se-Indonesia. Pada Penelitian lanjutan ini berfokus pada penambahan dan pengembangan konten materi uji sertifikasi pada asosiasi dan penerapan hasil platform kepada seluruh mahasiswa program studi Informatika di Indonesia berdasarkan skema kompetensi yang ada. Sesuai dengan peraturan Kemenristek nomor 44 tahun 2015 tentang Standar Nasional Pendidikan Tinggi, bahwa proses belajar mengajar mengacu kepada bentuk Student Learning Centered (SCL), dimana siswa harus aktif dalam proses belajar mengajar. Mahasiswa dinyatakan lulus berhak memperoleh ijazah,sertifikat profesi, dan sertifikat kompetensi. Sertifikat kompetensi diterbitkan oleh perguruan tinggi bekerjasama dengan organisasi profesi, lembaga pelatihan, lembaga sertifikasi profesi yang terakreditasi. Dari berbagai permasalahan terhadap Kelemahan-kelemahan yang ada, harus ada upaya untuk menyelesaikannya, munculnya konsep Open Course Ware (OCW) sebagai platform baru dibidang teknologi pendidikan memiliki beberapa karakteristik umum yang membedakan dengan manajemen sistem pembelajaran lainnya, diantaranya adalah (1) Offered Free, (2) No Register, (3) Openly Lisenced, (4) Accessible to anyone, (5) Extraordinary, penelitian ini diharapkan dapat membantu memberikan sumbangan sebagai solusi dalam meningkatkan kompetensi tenaga kerja indonesia, melalui Perancangan Open Course Ware (OCW) dalam penerapan content management application (CMA) untuk membantu persiapan uji kompetensi bagi mahasiswa yang berasal dari prodi informatika di Indonesia, metode perancangan system yang digunakan adalah metode prototype Hasil yang didapat berupa penerapan sebuah sistem yang terintegrasi dalam sebuah sisterm OCW yang menerapkan dan mengembangkan konten yang ada. Keywords ; Open Course Ware , Uji Sertifikasi, Kompetensi, Informatika, Teknologi Pendidikan